Development and Feasibility of an Animated Video for Nutrition Education Delivered via WhatsApp to Hemodialysis Patients - Yuana, Nabila Amartya; Pamungkasari, Eti Poncorini; Mulyani, Sri (Journal of Health and Nutrition Research, 2025)
Dietary management is very important for patients with chronic renal failur Dietary management is very important for patients with chronic renal failure. The problem that often occurs in patients with chronic renal failure is malnutrition, especially protein energy malnutrition. This study aims to analyze the acceptability of video through WhatsApp broadcasts as a medium for nutritional education for hemodialysis patients. This type of research uses the Research and Development method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The ADDIE model is structured with a systematic description of activities so that it fits the needs and characteristics required. The media feasibility assessment was carried out by assessing the validity of the animated video by three expert validators, namely material experts, media experts and linguists. The results of the media feasibility test by the expert team averaged 3.52 with a very valid category with minor revisions. Then a small group test was conducted consisting of 8 hemodialysis patients with purposive sampling with inclusion and exclusion criteria. The results of the small group test assessment were 95.91% in the category of very feasible and did not need revision. Based on the results of this analysis, the development of animated video media through whatsapp broadcasts can be given to hemodialysis patients as a medium for nutrition education and approved by a team of experts.